IMPLEMENTASI PENGELOLAAN ADMINISTRASI PENDIDIKAN DI RA - Ainin Ditya; Armanila, Amirah Syarifah Sirait, Najwa Mahfuza, Putri Puspita Hasri (CV. ADIBA AISHA AMIRA, 2023)
Schools serve as educational institutions equipped with necessary resources to fulfill their roles in enhancing the quality of school management. Competitions are organized in each school to nurture and produce high-caliber students. The school's excellence significantly impacts the quality of its students. This study employs library research, a method involving the collection of data or scholarly writings specifically focused on the research subject or bibliographic data. It entails a meticulous and in-depth analysis of pertinent library materials. Furthermore, the researcher employed quantitative techniques to gather pertinent information. Quantitative research aims to test hypotheses by collecting measurable data using statistics, mathematics, and computer science. The research endeavors to explore how the management of educational administration in schools enhances the effectiveness of learning, especially in early childhood education levels (PAUD/TK/RA).